US and UAE power play gains traction: Abu Dhabi sovereign wealth-backed entities pledge major US investment. - AGUINALDO, JENNIFER (MEED Business Review, 2025)
Abu Dhabi-based ADQ and US' Energy Capital Partners have formed a 50:50 partnership to invest up to $25bn in new power generation plants in the US. This agreement follows a meeting between US President Donald Trump and UAE national security adviser Sheikh Tahnoon Bin Zayed Al-Nahyan. The UAE is committed to strengthening economic ties with the US through investments in AI, technology, infrastructure, energy, and healthcare. This partnership marks the second major investment by an Abu Dhabi-based entity in the US, with a focus on AI infrastructure.